Website Based Cibendung Village Information System Design - Triyadi, Evan; Sigit Sugiyanto (Politeknik Piksi Ganesha Indonesia, 2024)
The design of the Cibendung Village information system aims to manage, access and record Cibendung Village so that information about Cibendung Village so that the information presented is important, up-to-date, interesting information and has become a lot of public attention to be more open. Therefore, the Cibendung Village Website has information features about media and communication about Cibendung Village. This feature is to get a lot of information to people who are more open than other social media such as Facebook, Twitter, Instagram and others and easy access to the website. Therefore, a web-based Cibendung Village Website was created using the waterfall method. This waterfall model provides sequential software starting from data analysis, design, coding, and testing implementation. After going through these stages, A Website-based Cibendung Village website was created to retrieve data, manage the website and access the website online to facilitate website access and get related information about Cibendung Village.